Implementation of Digital Marketing in increasing sales at PT. Kombas Digital Internasional Commissioner and Young Berjaya Group Kebumen - Sunhaji, Sunhaji; Aminudin Aziz, Fathul; Borham, Abd Shakor (Advances in Humanities and Contemporary Studies, 2024)
This research aims to determine the implementation of digital marketing to increase sales by PT. Kombas Digital International Commissioner and Young Berjaya Group Kebumen. This research is motivated by the fact that there are still many companies operating in the digital sector that have been running and achieving success, but have experienced bankruptcy along the way. This research is field research with a qualitative approach with descriptive qualitative methods. Primary data sources in this research come from directors, division heads and employees. The data collection techniques used were interviews, observation, documentation and literature study. Data analysis techniques are carried out by inventorying or data collection, identification, analysis and interpretation. The research results show that the implementation of digital marketing increases sales at PT. Kombas Digital International Commissioner and Muda Berjaya Kebumen Group use 4 digital media platforms including 1) website by creating website articles, advertising the website and optimizing the website on Google and Google Ads, as well as creating a website according to keywords every day; 2) social media by following live TikTok social media trends, using paid advertising, creating interesting content and including clear contact information so that it is easy and quick to contact; 3) market place is carried out by optimizing the marketplace and 4) paid advertising by providing discounts or live streaming vouchers.